Milestones and New Frontiers in Deep Learning - Serpa, Ygor Rebouças; Pires, Leonardo Augusto; Rodrigues, Maria Andréia Formico (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and Images, 2019)
Only very recently, deep learning models have been globally used as the basis for most of the on-going research on several fundamental computing areas, such as computer vision, information extraction, data generation and data understanding. The field is still a black box for many people, particularly, on its more mathematical aspects. Users of high level packages often struggle to understand the reasoning behind the many building blocks of deep learning, such as convolutional layers, batch normalization and activation functions.